The Role of KCNQ1 Mutations and Maternal Beta Blocker Use During Pregnancy in the Growth of Children With Long QT Syndrome - Huttunen, Heta; Hero, Matti; Lääperi, Mitja; Känsäkoski, Johanna; Swan, Heikki; Hirsch, Joel A.; Miettinen, Päivi J.; Raivio, Taneli (Frontiers in Endocrinology, 2018)
Objective: Two missense mutations in KCNQ1, an imprinted gene that encodes the alpha subunit of the voltage-gated potassium channel Kv7.1, cause autosomal dominant growth hormone deficiency and maternally inherited gingival fibromatosis. We evaluated endocrine features, birth size, and subsequent somatic growth of patients with long QT syndrome 1 due to loss-of-function mutations in KCNQ1. Design: Medical records of 104 patients with LQT1 in a single tertiary care center between 1995 and 2015 were retrospectively reviewed. Methods: Clinical and endocrine data of the LQT1 patients were included in the analyses. Results: At birth, patients with a maternally inherited mutation (n=52) were shorter than those with paternal inheritance of the mutation (n=29) (birth length, -0.70 ± 1.1 SDS vs. -0.2 ± 1.0 SDS, P<0.05). Further analyses showed, however, that only newborns (n=19) of mothers who had received beta blockers during pregnancy were shorter and lighter at birth than those with paternal inheritance of the mutation (n=29) (-0.89 ± 1.0 SDS vs. -0.20 ± 1.0 SDS, P<0.05; and 3173 ± 469 g vs. 3515 ± 466g, P<0.05). Maternal beta blocker treatment during the pregnancy was also associated to lower cord blood TSH levels (P=0.011) and significant catch-up growth during the first year of life (Δ0.08 SDS/month, P=0.004). Later childhood growth of the patients was unremarkable. Conclusions: Loss-of-function mutations in KCNQ1 are not associated to abnormalities in growth, whereas maternal beta blocker use during pregnancy seems to modify prenatal growth of LQT1 patients – a phenomenon followed by catch-up growth after birth.